Revision of the cricket subfamily Podoscirtinae Saussure, 1878 (Orthoptera: Gryllidae) from China - Zheng, Yanna; Xin, Zhixia; Xie, Lingde; Ma, Libin (Zootaxa, 2021)
The article revised Chinese Podoscirtinae species. Three new species of Aphonoides Chopard, 1940 were reported. Two species of the genera of Aphonoides Chopard, 1940 and Mistshenkoana Gorochov, 1990 were firstly recorded from China. Six synonyms of the genera of Zvenella Gorochov, 1988 and Phyllotrella Gorochov, 1988 were proposed. All species mentioned above and some relevant taxa were described and illustrated, and keys as well as distribution map were provided.